Autonomous control mechanism of stator assembly in the bacterial flagellar motor in response to changes in the environment. Issue 6 (16th September 2018) - Minamino, Tohru; Terahara, Naoya; Kojima, Seiji; Namba, Keiichi
Summary: The bacterial flagellar motor is composed of a rotor and a transmembrane ion channel complex that acts as a stator unit. The ion channel complex consists of at least three structural parts: a cytoplasmic domain responsible for the interaction with the rotor, a transmembrane ion channel that forms a pathway for the transit of ions across the cytoplasmic membrane, and a peptidoglycan‐binding (PGB) domain that anchors the stator unit to the peptidoglycan (PG) layer. A flexible linker connecting the ion channel and the PGB domain not only coordinates stator assembly with its ion channel activity but also controls the assembly of stator units to the motor in response to changes in the environment. When the ion channel complex encounters the rotor, the N‐terminal portion of the PGB domain adopts a partially stretched conformation, allowing the PGB domain to reach and bind to the PG layer. The binding affinity of the PGB domain for the PG layer is affected by the force applied to its anchoring point and to the type of ionic energy source. In this review article, we will present current understanding of autonomous control mechanism of stator assembly in the bacterial flagellar motor. Abstract : The flagellar motor is composed of a rotor and a dozen stator units and autonomously controls the assembly of stator units in the motor in response to changes in the environment. Here we will describe our current understanding of the autonomous stator assembly mechanism.